Surgical treatments of metastatic bone disease of the hip joint: a scoping review protocol - Jiling Liu; Li Mao; Zhenxiao Yang; Chiheng Yan; Dagang Feng (BMJ Open)
Introduction Metastatic disease of the hip causes severe pain and is a serious threat to the patient’s motor function. Surgery is required, but the actual efficacy is unclear, and there are many concerns for both patients and doctors. The purpose of this protocol is to conduct a scoping review for helping decisions of the intended audience.Methods and analysis This scoping review will be conducted according to the framework proposed by Arksey and O’Malley and reported in accordance with Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols Extension for Scoping Reviews criteria. To answer our research questions, we will search Chinese and English databases using appropriate search terms, comb through clinical studies on surgical procedures for metastatic bone disease of the hip and incorporate visual charts and graphs to provide a comprehensive analysis and evaluation of the literature according to the criteria for basic characteristics, interventions and outcome indicators.Ethics and dissemination Since the data are publicly available, no ethical approval or participant consent is required. The results of the review will be published in an open-access peer-reviewed journal and presented at national and international conferences.